Zimbabwe : Staff Monitored Program. (IMF Staff Country Reports; Country Report ;, 2013)
This staff report for Zimbabwe highlights the key macroeconomic challenges of taking steps to improve fiscal and external sustainability and increase financial sector stability. Zimbabwe has made good progress in restoring macroeconomic stability since the end of hyperinflation in 2009, but the economic rebound is waning, and key challenges need to be tackled. Strong policies are needed to sustain the economic recovery, restore fiscal and external sustainability, and increase financial stability. This would place the economy on a long-term, sustained inclusive growth path. Implementation of indigenization and empowerment policies according to transparent rules, with due respect to property rights, remains essential to build investor confidence and attract needed foreign direct investment.